Extending morphometric scaling relationships: the role of bankfull width in unifying subaquatic channel morphologies - Hasenhündl, Martin; Bauernberger, Lena Sophie; Böhm, Christoph (Frontiers in Earth Science, 2023)
Subaquatic channels, situated in lakes, fjords, submarine canyons and on deep-sea fan systems, exhibit diverse morphometric characteristics controlled by sediment transport processes, particularly turbidity currents. These processes play a significant role in transporting sediment, organic carbon, nutrients, and pollutants and pose hazards to critical infrastructure. This study examines a balanced set of subaquatic channels across various settings, sizes, and locations, employing novel data harmonization techniques to address biases toward larger channels. The analysis reveals consistent scaling relationships, particularly the dominant role of bankfull width, influencing bankfull depth, cross-sectional area, wavelength, and amplitude. The aspect ratio (width-to-depth) emerges as a significant parameter, reflecting a necessary channel compactness to maintain turbidity currents. Meandering development reveals relations between width, wavelength, and amplitude, with a preference for specific ratios. Meandering is most pronounced at channel beginnings, transitioning to straighter forms downstream, potentially influenced by flow dynamics and flow confinement. The study broadens the understanding of subaquatic channel evolution, emphasizing the importance of bankfull width and providing insights applicable across settings and scales.